2011
DOI: 10.1038/hdy.2011.108
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations and the evolution of photoperiodic time measurement within a local population of the pitcher-plant mosquito, Wyeomyia smithii

Abstract: The genetic relationship between the daily circadian clock and the seasonal photoperiodic timer remains a subject of intense controversy. In Wyeomyia smithii, the critical photoperiod (an overt expression of the photoperiodic timer) evolves independently of the rhythmic response to the Nanda-Hamner protocol (an overt expression of the daily circadian clock) over a wide geographical range in North America. Herein, we focus on these two processes within a single local population in which there is a negative gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…A trait related to circadian rhythms in Nasonia is photoperiodism, apparent in the form of diapause induction in short days [15], [44], [45]. Whether the circadian system in insects, apparent in overt circadian rhythms, and photoperiodism rely on a unique genetic system comprising canonical clock genes or whether these affect both phenotypes through different pathways is still unclear [19], [46], [47]. While it is undisputed that both systems share components (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A trait related to circadian rhythms in Nasonia is photoperiodism, apparent in the form of diapause induction in short days [15], [44], [45]. Whether the circadian system in insects, apparent in overt circadian rhythms, and photoperiodism rely on a unique genetic system comprising canonical clock genes or whether these affect both phenotypes through different pathways is still unclear [19], [46], [47]. While it is undisputed that both systems share components (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic variation in circadian genes should not be extrapolated to photoperiodism, and modern genetic approaches should be used to identify genes involved in photoperiodism (Bradshaw et al 2012;Emerson et al 2009;Bradshaw and Holzapfel 2008;Bradshaw et al 2003). Lankinen and Forsman (2006) do present further data on this line using Drosophila litoralis and Drosophila montana (Lankinen et al 2013) from different latitudes and refer to older publications (see furthermore Koštál 2011;Takeda and Skopik 1997;Skopik and Takeda 1986).…”
Section: Photoperiodism: Hourglass or Oscillator?mentioning
confidence: 96%
“…3,16 There remains no conclusive evidence defining the photoperiodic control of diapause in insects; in fact, there is an intense controversy regarding Bünning's hypothesis. [17][18][19][20] The genetic and metabolic components of photoperiodic responses vary among insect species, and diapause appears to have evolved independently numerous times, thus, we anticipate that not all photoperiodic clocks of insects will interact with circadian clocks in the same fashion. 21 Our previous experiments on photoperiodic responses under non-24-h light-dark cycle revealed that when the length of photophase exceeded the critical day length (13.5 h), diapause was inhibited effectively regardless of the duration of the accompanying dark component ( Figure 5 in the study by He et al) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The central importance of night length was also seen in data for the flesh fly Sarcophaga argyrostoma (Robineau-Desvoidy) 5 in which the incidence of pupal diapause was very low in cycles containing a short night (eg, LD 12:8 and LD 16:8) with non-24-h light-dark cycles in which photophases of 10, 12, 14, and 16 h were combined with different lengths of scotophase of 4-24 h have been carried out on the zygaenid moth Pseudopidorus fasciata (Felder & Felder, 1862), the pine caterpillars Dendrolimus punctatus (Walker), the rice stem borer Chilo suppressalis (Walker), the Asian corn borer Ostrinia furnacalis, and the fall webworm Hyphantria cunea in our laboratory. [6][7][8][9][10] The photoperiodic response curves in these species all showed that the incidence of larval diapause was low or zero in cycles containing a short night (4 and 8 h), but high in cycles containing a long night (12,16,20, and 24 h), regardless of the length of the photophase, indicating that the length of the scotophase plays an essential role in the determination of diapause in these species.…”
Section: Introductionmentioning
confidence: 99%